Synergistic effects of sesame oil, extra virgin olive oil, psyllium extract, and dandelion extract on cholesterol gallstone dissolution: An in vitro comparative study against Rowachol® - Raghad Serri; Nada Dehneh; Mohammad Ghannam; Mohamad Radwan Sirri (PLoS ONE, 2025)
Background Cholesterol gallstones represent a significant global health burden. Current treatments, including surgery and oral dissolution agents, are often invasive or limited by side effects and variable efficacy. This study investigated the in vitro gallstone-dissolving efficacy of a natural combination—sesame oil (SO), extra virgin olive oil (EVOO), psyllium extract (PE), and dandelion extract (DE)—compared to the pharmaceutical agent Rowachol®. Methods In a randomized in vitro study, seventy cholesterol-dominant human gallstones were assigned to seven groups receiving either individual agents, multi-component combinations, or Rowachol® (control). Two prespecified endpoints were assessed under standardized simulated bile conditions at 48 h (T1), 96 h (T2), and 144 h (T3): dissolution rate (DR, %; weight loss) and cumulative cholesterol release (mg). Statistical analyses compared groups across time and explored potential multi-component interactions. Results The four-component regimen (G6: PE + DE+SO+EVOO) showed the greatest efficacy at T3, achieving DR = 92.57% ± 4.2 and cholesterol release = 114.48 ± 4.2 mg, significantly exceeding Rowachol® (39.71% ± 1.9; 42.57 ± 1.9 mg; p < 0.001) and all other groups. Effects were time-dependent, with progressive separation from T1 to T3. Key bioactive compounds—oleic acid, taraxacin, arabinoxylan, and linoleic acid—showed strong positive correlations with dissolution outcomes (r = +0.76 to +0.94). A regression model identified these compounds as primary efficacy predictors, accounting for 94% of the observed variance (adjusted R² = 0.94). Conclusions Under short-term, controlled in vitro conditions, the SO+EVOO+PE + DE combination achieved a ~ 2.3-fold higher dissolution rate than Rowachol® at 144 h. These findings constitute mechanistic, hypothesis-generating evidence that clarifies how dissolution may be enhanced ex vivo. Confirmation in well-designed in-vivo models—followed by clinical studies to evaluate safety, dosing, and effectiveness—is required before any patient-care application.